2021
DOI: 10.1080/20008198.2020.1864949
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and posttraumatic growth mediate the relations between social support, prosocial behavior, and antisocial behavior among adolescents after the Ya’an earthquake

Abstract: Background: Previous studies indicate that social support, self-compassion, and posttraumatic growth (PTG) can affect prosocial behaviour and antisocial behaviour, but few studies have examined their combined role in prosocial and antisocial behaviour among adolescents who have experienced traumatic events. Objective: This study examined the mediating roles of self-compassion and PTG in the relationship between social support and prosocial and antisocial behaviour among Chinese adolescents after the Ya'an eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 80 publications
5
22
0
Order By: Relevance
“…As one of the dimensions of our social connection component, compassion has been associated with greater wellbeing and resilience in the face of adversity [ 53 , 61 , 115 ]. In particular, our study expands on current evidence revealing that self-compassion is associated with greater post-traumatic growth in the context of traumatic events [ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As one of the dimensions of our social connection component, compassion has been associated with greater wellbeing and resilience in the face of adversity [ 53 , 61 , 115 ]. In particular, our study expands on current evidence revealing that self-compassion is associated with greater post-traumatic growth in the context of traumatic events [ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 72%
“…Hence receiving compassion (from others and from oneself) can act as a protective factor during difficult times. In the context of traumatic events, self-compassion has been linked to greater post-traumatic growth [ 62 , 63 ], and associated with less post-traumatic stress symptomatology, with tentative evidence suggesting that compassion interventions potentially reduce PTSD symptoms [ 64 ]. It has been suggested that some of the possible mechanisms between the protective effects of social support and compassion on reduced PTSD might be lower psychological inflexibility [ 65 ], emotional dysregulation [ 66 ] and avoidance strategies [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, burn-related PTG studies found that burn survivors had a greater appreciation for their health and well-being, as well as for family and friends (McLean et al, 2015;Martin et al, 2016). Evidence from collective traumatic events studies also reported a positive association between PTG and prosocial behaviour and altruism among refugees exposed to violence (Canevello et al, 2021) and adolescents who experienced earthquake (Liu et al, 2021). It was clear that the reminder of one's mortality drove appreciation of the present moment, with regard to both one's own personal and spiritual growth as well as the wellbeing of others.…”
Section: Mediating Roles Of Personal Valuesmentioning
confidence: 99%
“…Verbal abuse and emotional neglect in childhood from their parents would make children treat themselves in this way their parents treat them thereby form a self-cognitive model of low value [31]. Individuals are prone to form negative selfattitudes, which may damage the ability of self-compassion and affect adolescent problem behaviors [32][33][34].…”
Section: The Mediating Role Of Self-compassionmentioning
confidence: 99%